Algorithmic threats to journalism: the logics of digital platforms and artificial intelligence as (non-) references for the production and circulation of news. - Landim de Souza, Gabriel; da Silva Coutinho, Iluska Maria (Razón y Palabra)
In a Platform Society (Helmond, 2015), citizens make decisions and form opinions through digital social networks. The affordances (Gibson, 1977) of platforms have impacted journalism’s production routine. Media companies have started to submit to algorithmic logic (Barros et al., 2021; Gillespie, 2018) and the possibilities allowed by artificial intelligence (Sichman, 2021) to share news. We sought to understand how journalism deals with algorithmic mediation without losing control over its content. We combined bibliographical research with a documentary survey of the editorial principles of Grupo Globo, one of Brazil’s leading media companies, which has updated its use policies of artificial intelligence in journalism. Using Audiovisual Materiality Analysis (Coutinho, 2018), which aims to identify narrative conflicts and productions of meaning, we carried out empirical research with a report broadcast on TV Globo’s Jornal Nacional, which addresses the updating of editorial principles, to understand how the group publicizes the issue. We found that faced with the risk of losing control over the circulation of their content and taking into account the lack of transparency of digital mechanisms, the outlet highlighted the role of the journalist in finalizing texts mediated by algorithms and publicly reinforced this commitment. It is necessary to understand the new forms of threat to the press, veiled by computer codes.